Euneophytes of the urban flora of the Kyiv urban area: new findings, additions and clarifications (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Locations: Kyiv urban agglomeration, 13534 км². Methods: field observations, critical analysis of literature data, and analysis of the iNaturalist platform. Nomenclature: https://powo.science.kew.org Results: The newest addition to the species composition of the flora of the Kyiv urban area, registered during 2000–2024, is considered. Information is provided for the following 47 species and hybrids: Acer monspessulanum, Allium nutans, A. rosenorum, Cardamine hirsuta, C. occulta, Castanea sativa, Chaerophyllum nodosum, Chrozophora tinctoria, Coreopsis tinctoria, Cosmos sulphureus, Сotoneaster acutifolius, Crataegus submollis, Cydonia oblonga, Cymbalaria muralis, Eleutherococcus senticosus, Eriochloa villosa, Equisetum ×moorei, E. ramosissimum, Exochorda racemosa, Fumaria rostellata, Galatella sedifolia subsp. dracunculoides, Gymnocarpium robertianum, Hedera canariensis, Helleborus orientalis, H. purpurascens, H. caucasicus ×H. purpurascens, Hesperis matronalis, Hylotelephium spectabile ×H. telephium s. l. 'Herbstfreude', Kickxia spuria, Knautia macedonica, Koelreuteria paniculata, Lepidium campestre, Limonium sinuatum, Lonicera caprifolium, L. maackii, Mesembryanthemum cordifolium, Muscari armeniacum, Oenothera pilosella, Phedimus aizoon, Prunus persica, Rubus hirtus, Rumex kioviensis, Sedum album, Smyrnium olusatrum, ×Sorbaronia fallax, Stellaria neglecta and Taxus × media. The South European Knautia macedonica is reported for the first time for the Kyiv urban agglomeration flora; two North American anthropophytes are reported: Coreopsis tinctoria, Cosmos sulphureus; tropical Mesembryanthemum cordifolium, previously omitted Equisetum ramosissimum and locations for 9 species were supplemented. According to the attributive categories, eunеophytes are within the framework typical for the spontaneous flora of alien species of the Kyiv urban agglomeration. This is confirmed, for example, by the presence of 5 interspecific and 1 intergeneric hybrid combinations among the newest eunеophytes.
Keywords: biodiversity, taxonomic and typological categories, migration capacity, Ukraine